Exchange project: images of history in Bulgaria and Austria (winter semester 2022/23) - Dyballa, Jacqueline (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
The article presents the follow-up project of the intercultural and interdisciplinary exchange project for German language and literature students at Sofia University and history students at the Alpen-Adria-Universität Klagenfurt on the topic of historical images and memory culture. After a short presentation of how history is presented in German as a foreign language textbooks at Bulgarian schools, the project Images of History in Bulgaria and Austria will be described. The project is then evaluated from the point of view of some of the students, based on reports of their experiences and their results. The article aims to encourage similar international projects in German studies abroad and to promote historical awareness in the classroom.
Keywords: online language project; history images; intercultural exchange; history awareness